PENGARUH PROVIDER TERHADAP PENGGUNAAN ALAT SISTEM KEAMANAN SEPEDA MOTOR JARAK JAUH MENGGUNAKAN DINAMO MOTOR LISTRIK 5 V DC - Edy Setyawan; Fadelan Fadelan; Nanang Suffiadi Akhmad (KOMPUTEK, 2019)
Cases of motor vehicle theft are still common in the environment around us. The main cause is the knowledge of criminals, the dominant motorcycle security system is the same in every other motorcycle unit that uses a steering handlebar safety lock. Therefore the need for additional safety systems is felt very necessary to avoid motor vehicle theft. From the four tests conducted, the level of accuracy of location scanning by GPS experienced a difference in each test, this is due to the strength of the network received by the GPS device between the two devices, both from the researchers' GPS device and the GPS device attached to the vehicle unit, decreasing the relative accuracy between 6.8% and 17% in testing. The speed of response of the safety device is very dependent on the signal strength and the place where the vehicle or vehicle owner is owned by each provider, from the test delay calls are 3,2 seconds results,it was concluded that TELKOMSEL providers who have a more stable network.This is evidenced by the difference in the time of receipt of the response of vehicle safety devices when testing telephone delay calls and GPS testing. The advantage of this tool is that the assembling of components is quite simple compared to other electrical safety devices so that it is easy to peruse